"Green washing" or "authentic effort"? An empirical investigation of the quality of sustainability reporting by banks. Issue 2 (9th November 2020) - Khan, Habib Zaman; Bose, Sudipta; Mollik, Abu Taher; Harun, Harun
Abstract : Purpose: This study explores the quality of sustainability reporting (QSR) and the impact of regulatory guidelines, social performance and a standardised reporting framework (using the Global Reporting Initiative [GRI] guidelines) on QSR in the context of banks in Bangladesh. Design/methodology/approach: Using a sample of 315 banking firm-year observations over 13 years (2002–2014), a content analysis technique is used to develop the 11-item QSR index. Regression analysis is used to test the research hypotheses. Findings: Initially, QSR evolved symbolically in Bangladesh's banks but, over our investigation period, with QSR indicators gradually improving, the trends became substantive. The influences on QSR were sustainable banking practice regulatory guidelines, social performance and use of the GRI guidelines. However, until banks improve reporting information, such as external verification and trends over time, QSR cannot be regarded as fully substantive. Research limitations/implications: This study advances QSR research and debate among academic researchers. With regulatory agencies and stakeholders increasingly using sustainability reporting information for decision making, the information's quality is vital. Originality/value: This study is the first on QSR in the banking industry context, with previous research mostly investigating the quantity of sustainability reporting. The current study also synthesises QSR with sustainability regulation and social performance factors which have rarely been used in the sustainability literature. To gain a holistic understanding of QSR, existing QSR measures are advanced by combining external reporting efforts with banks' internalisation initiatives.